ANALISIS BUSINESS LEVEL STRATEGY DAN DIVERSIFICATION PERUSAHAAN SAMSUNG - Wilyanto, Adi; Renaldi, Angelina Julia; Valentina, Eni; Richmond, Richmond; Melinda, Rieza; Fatyandri, Adi Neka (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
The writing of the article